2021
DOI: 10.3390/agriculture11101007
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Cost-Benefit Analysis of Using Pesticidal Plants in Smallholder Crop Protection

Abstract: Assessing the potential drivers of farmers using pesticidal plants for crop protection is essential for wider adoption. However, few studies have focused on collaborative assessments of the underlying trade-offs when using pesticidal plant extracts for pest control. Smallholder farmers in northern Tanzania involved in farmer driven research assessing pesticidal plants evaluated the costs, benefits, trade-offs and areas for future investment. A questionnaire was used to collect demographic information from 77 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Further, Belmain et al (2022) suggest the elimination of synthetic pesticides in order to support these natural processes and food sovereignty. Mkindi et al (2021) recommend pesticidal plants as one alternative to synthetic pesticides. Onethird of farmers in the study area reported using pesticidal plants such as T. vogelii and Tithonia diversifolia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Belmain et al (2022) suggest the elimination of synthetic pesticides in order to support these natural processes and food sovereignty. Mkindi et al (2021) recommend pesticidal plants as one alternative to synthetic pesticides. Onethird of farmers in the study area reported using pesticidal plants such as T. vogelii and Tithonia diversifolia.…”
Section: Discussionmentioning
confidence: 99%
“…There is renewed interest in the use of pesticidal plants along with soil health improvement to better manage insect pests and diseases (Belmain et al, 2022). Common bean smallholder farmers in our study area use pesticidal plants for controlling insect pests and diseases, mainly targeting above-ground pests and diseases (Mkindi et al, 2021) as there is little evidence of the use and efficacy of such products on below-ground pests and pathogens (Toepfer et al, 2021). Further, more needs to be known in African smallholder systems on how soil type, soil quality and farmer management of soil health and fertility contribute to SPD, although studies from other areas show some promising findings (Watson et al, 2002;Janvier et al, 2007;Birkhofer et al, 2008;Huber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Isman, 2020;Uyi et al, 2021;Ngegba et al, 2022) including FAW (Phambala et al, 2020;Rioba and Stevenson, 2020). Research on the efficacy of botanicals (Mkindi et al, 2017), their environmental safety (Tembo et al, 2018), cost-benefits (Amoabeng et al, 2014;Mkenda et al, 2015) and farmer-perceived benefits to health (Mkindi et al, 2021) highlight their agroecological importance, particularly within smallholder farming systems (Isman, 2008;Belmain et al, 2022). Botanical pesticides are typically formulated as liquids to spray on to crops.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Belmain et al (2022) suggest the elimination of synthetic pesticides in order to support these natural processes and food sovereignty. Mkindi et al (2021) recommend pesticidal plants as one alternative to synthetic pesticides. Onethird of farmers in the study area reported using pesticidal plants such as T. vogelii and Tithonia diversifolia.…”
Section: Discussionmentioning
confidence: 99%
“…There is renewed interest in the use of pesticidal plants along with soil health improvement to better manage insect pests and diseases (Belmain et al, 2022). Common bean smallholder farmers in our study area use pesticidal plants for controlling insect pests and diseases, mainly targeting above-ground pests and diseases (Mkindi et al, 2021) as there is little evidence of the use and efficacy of such products on below-ground pests and pathogens (Toepfer et al, 2021). Further, more needs to be known in African smallholder systems on how soil type, soil quality and farmer management of soil health and fertility contribute to SPD, although studies from other areas show some promising findings (Watson et al, 2002;Janvier et al, 2007;Birkhofer et al, 2008;Huber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%